The Babri Masjid question, 1528-2003 :'a matter of national honour' - Noorani, Abdul Gafoor Abdul Majeed (Tulika Books, 2003)
History of Babri Masjid of Ayodhya (Faizabad, India) through its demolition and resultant litigation in various fora; contributed articles and documents.